Security Evaluation for RFID System: Security Evaluation Index Architecture and Evaluation Model - Hengfeng Luo; Ruiqi Liu; Yingkai Wang; Jinghao Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the rapid development and application of RFID system, people would pay more attention to the security of RFID, which is the essential issue and key technology in RFID system. This paper establishes the evaluation index architecture of RFID security, then according to these indexes for the evaluation of the RFID system security which based on fuzzy synthetic evaluation model, this paper proposes a AHP (The Analytic Hierarchy Process) for weighs, and then applies fuzzy comprehensive evaluation method for more accurate and effective evaluation results, which is used to evaluate the security of RFID system. Our security evaluation index architecture and evaluation model with RFID system is very practical and effective in the real life. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5401